2012
DOI: 10.1021/ja208338j
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Matrix Metalloproteinase 1-Catalyzed Collagenolysis

Abstract: The proteolysis of collagen triple-helical structure (collagenolysis) is a poorly understood yet critical physiological process. Presently, matrix metalloproteinase 1 (MMP-1) and collagen triple-helical peptide models have been utilized to characterize the events and calculate the energetics of collagenolysis via NMR spectroscopic analysis of 12 enzyme-substrate complexes. The triple-helix is bound initially by the MMP-1 hemopexin-like (HPX) domain via a four amino acid stretch (analogous to type I collagen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
216
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(240 citation statements)
references
References 87 publications
(221 reference statements)
21
216
1
2
Order By: Relevance
“…We propose that mammalian collagenases do not serve merely as passive acceptors of spontaneously occurring unfolded collagen states (44,45), but they promote a local perturbation of the triple helix that facilitates collagenolysis. The recently reported NMR study supports this notion by demonstrating a weakening of the collagen interchain contacts in the complex with MMP-1 (19).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…We propose that mammalian collagenases do not serve merely as passive acceptors of spontaneously occurring unfolded collagen states (44,45), but they promote a local perturbation of the triple helix that facilitates collagenolysis. The recently reported NMR study supports this notion by demonstrating a weakening of the collagen interchain contacts in the complex with MMP-1 (19).…”
Section: Discussionsupporting
confidence: 54%
“…6) differs from that derived from NMR experiments (19) in that it does not require a separation of the Cat and Hpx domains. Bertini et al (19), who also used the E200A mutant of MMP-1, found that the Cat domain interacted mainly with the L chain and the Hpx domain mainly with the L and M chains.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In TTD, we found a cell type-specific transcription overexpression of the matrix metalloproteinase 1 (MMP-1), a gene encoding a zinc-containing endopeptidase that plays a key role in physiological and pathological tissue remodeling (20)(21)(22)(23). The MMP-1 transcription up-regulation results in high secretion of the active MMP-1 enzyme and subsequent degradation of collagen type I (COL1) in cell/tissue cultures, as well as in patient skin.…”
mentioning
confidence: 99%